Strategic decisions: How good does it fit the decision-making process into the strategic management process? - Kolar Edvard; Tušak Matej; Robnik Petra; Biloslavo Roberto (Journal of Engineering Management and Competitiveness)
The complicated dance between the decision-making (hereinafter: DM) process, which is shaped by the individual psychological constructs and internal cognitive processes, and the methodological process of strategic management (hereinafter: SMP), which can be understood as a framework that defines decision context, raises pertinent questions about their coherence. The purpose of this study is to propose an integrative model of the strategic decision-making process (hereinafter: SDM), which links the cognitive processes of decision-makers with the rigour of strategic management and identifies and mitigates potential risks at each stage of the holistic process. To design the research, we used the "model paper" approach which seeks to build a theoretical framework that predicts relationships between research concepts. The developed comprehensive model connects four independent concepts, creating a holistic framework for SDM in organizations. The comprehensive model reveals a high degree of consistency between the SMP, knowable decision-making cycle and cognitive processes. Throughout the entire process, decision-makers need to be mindful of the interplay between System 1 and System 2 thinking. While System 1 thinking may provide quick insights and initiate creative thinking, it is important to complement it with the deliberate and analytical reasoning of System 2 thinking, which can be supported by a proper application of different strategic management tools and methods.